When Is the Time to Hate? A Research Review on the Impact of Dramatic Events on Islamophobia and Islamophobic Hate Crimes in Europe - Borell, Klas (Islam and Christian-Muslim relations, 2015)
Social scientists have long been interested in the significance of unexpected, dramatic events for social change. However, when it comes to research on prejudice and hate crimes, the impact of sudden, dramatic events has been little considered. The purpose of this research review is to survey European data to elucidate the temporal links between unexpected events, prejudice, and hate crimes, and also to pinpoint some of the methodological problems faced by scholars studying the impact of unanticipated dramatic events on prejudice and hate crimes; the significance of unexpected events often leaves researchers without access to relevant baseline data. The studies of Islamophobia and Islamophobic hate crimes considered in the present article privilege a dynamic view of time: terrorist attacks instill a sense of uncertainty and risk and Islamophobia and hate crimes are to a large extent event-driven and reactive, and tend to flare up on the heels of dramatic events. The recent attention paid to the role of unexpected, dramatic events represents a new and very promising approach to the study of prejudice and hate crimes; with the earlier, essentially spatial research focus now complemented by a temporal focus, the chances increase of charting the underlying dynamics and causes of prejudice and hate crimes.